Tinjauan Teologis – Psikologis Gaya Praise & Worship Gereja Denominasi Kharismatik bagi Kehidupan Rohani Jemaat - Purwonugroho, Daniel Pesah; Susanti, Ruth Natalia (Jurnal Ap-Kain, 2024)
The distinctive value of charismatic churches lies in their approach to the experience of praise and worship, characterized by a unique style. Music plays a crucial role in charismatic churches, serving as the foundation of their worship practices. In addition to music, bodily movements are commonly observed and considered a natural expression in the worship style of charismatic churches. The incorporation of bodily movements adds a tactile and visual dimension to the spiritual experience of the congregation. This particular style of praise and worship not only deepens the faith of the congregation but also has the potential to positively impact their mental well-being. By engaging in this worship style, congregants can achieve a profound sense of spiritual fulfillment and heightened awareness of God's presence. Moreover, participants often report experiencing a sense of internal renewal, along with increased positive emotions and emotional well-being when engaging in the worship activities of charismatic churches. Through qualitative and descriptive analysis, the author seeks to examine various aspects of praise and worship in charismatic churches. It is evident that the charismatic church's approach to praise and worship offers numerous benefits that contribute to the spiritual enrichment and overall well-being of its members. The positive and holistic effects of the charismatic church's praise and worship style on the spiritual life of the congregation are thoroughly explored in the author's review.AbstrakNilai khas gereja karismatik terletak pada pendekatannya terhadap pengalaman praise worship, yang ditandai dengan gaya yang unik. Musik memainkan peran penting dalam gereja karismatik, berfungsi sebagai landasan praktik ibadah mereka. Selain musik, gerak tubuh umumnya diamati dan dianggap sebagai ekspresi alami dalam gaya ibadah gereja karismatik. Penggabungan gerak tubuh menambah dimensi sentuhan dan visual pada pengalaman spiritual jemaat. Gaya praise worship khusus ini tidak hanya memperdalam iman jemaat tetapi juga memiliki potensi untuk berdampak positif pada kesejahteraan mental mereka. Dengan terlibat dalam gaya ibadah ini, anggota jemaat dapat mencapai rasa pemenuhan rohani yang mendalam dan kesadaran yang tinggi akan kehadiran Tuhan. Selain itu, peserta sering melaporkan mengalami rasa pembaruan internal, bersama dengan peningkatan perasaan positif dan kesejahteraan emosional ketika terlibat dalam kegiatan ibadah gereja yang karismatik. Melalui penelitian analisis kualitatif dan deskriptif, penulis berusaha untuk memeriksa berbagai aspek praise worhsip gereja karismatik. Jelas bahwa pendekatan gereja karismatik terhadap praise worship menawarkan berbagai manfaat yang berkontribusi pada pengayaan spiritual dan kesejahteraan keseluruhan anggotanya. Efek positif dan holistik dari gaya praise worship gereja karismatik terhadap kehidupan spiritual jemaat dieksplorasi secara menyeluruh dalam ulasan penulis.